Komunikasi Bimbingan Islam - Enjang AS (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
In the field of ilmu dakwah, guidance  counseling is one of the four professions of dakwah. Experts on ilmu dakwah suggest that there are at least  three methods of guidance and consouling: ahsan qaul (best words), hiwar  (dialogue), and khithabah (speech). The main objectives of these methods have been refreshing and stimulating the inner spiritual feelings as servants of God Besides, they also aim at helping clients overcome problems they are facing. These methods are oral in form and use the necessary apparatuses of communiation.As process of communication, guidance and consouling need a support from theories of communication to develop effective communication skills. 1bis paper asserts that the kind of communication fitting to this process of communication is interpersonal communication since it is involving two sides or more in a two-way traffic communication this is certainly different from that of mass communication which is involving ane-way communication. The earlier is a dialogue whereas the latter is a monologue.